A panel method for both marine propulsion and renewable energy - Xu, Yiyi; Liu, Pengfei; Penesis, Irene; He, Guanghua (Journal of Naval Architecture and Marine Engineering, 2019)
A computational hydrodynamics method was formulated and implemented as a tool from screw propeller propulsion to renewable energy performance prediction, design and optimization of horizontal axis turbines. As an example for tidal energy generation, a comparative analysis between screw propellers and horizontal axis turbines was presented, in terms of geometry and motion parameters, inflow velocity analysis and the implementation methodologies. Comparison and analysis are given for a marine propeller model and a horizontal axis turbine model that have experimental measurements available in literature. Analysis and comparison are presented in terms of thrust coefficients, shaft torque/power coefficients, blade surface pressure distributions, and downstream velocity profiles. The effect of number of blades from 2 to 5, of a tidal turbine on hydrodynamic efficiency is also obtained and presented. The key implementation techniques and methodologies are provided in detail for this panel method as a prediction tool for horizontal axis turbines. While the method has been proven to be accurate and robust for many propellers tested in the past, this numerical tool was also validated and presented for both tidal and wind turbines.